2008
DOI: 10.1161/circulationaha.108.788109
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Myocardial Perfusion Single-Photon Emission Computed Tomography and the Impact of Renal Function on Cardiac Death

Abstract: Background-Patients with chronic kidney disease (CKD) have worse cardiovascular outcomes than those without CKD. The prognostic utility of myocardial perfusion single-photon emission CT (MPS) in patients with varying degrees of renal dysfunction and the impact of CKD on cardiac death prediction in patients undergoing MPS have not been investigated. Methods and Results-We followed up 1652 consecutive patients who underwent stress MPS (32% exercise, 95% gated) for cardiac death for a mean of 2.15Ϯ0.8 years. MPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 44 publications
(94 reference statements)
5
67
1
1
Order By: Relevance
“…Our previous studies and those of others have suggested that MPI can help predict outcomes among patients with suspected or extant CAD and those with CKD. [10][11][12][13] Although the incidence and severity of CVD are increased in patients with CKD, 1,3 routine screening has not yet been implemented in clinical practice. In addition, optional time-frame for screening for CVD among patients with CKD has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies and those of others have suggested that MPI can help predict outcomes among patients with suspected or extant CAD and those with CKD. [10][11][12][13] Although the incidence and severity of CVD are increased in patients with CKD, 1,3 routine screening has not yet been implemented in clinical practice. In addition, optional time-frame for screening for CVD among patients with CKD has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…19 The MPI defect score was relatively lower than those previously reported. [10][11][12][13] Since we excluded patients with CKD who had CAD, such a small defect might impact cardiac events in patients without such a diagnosis.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In high-risk populations, as in those with diabetes mellitus (DM) or chronic kidney disease, MPI has been shown to be a powerful predictor of risk, but nevertheless, patients with normal myocardial perfusion are at higher risk than those without DM or chronic kidney disease. 2,3 Thus, there continues to be a need to extract more useful prognostic data from stress MPI especially in high-risk populations.…”
mentioning
confidence: 99%